Paparan Debu Kayu Dan Gangguan Fungsi Paru Pada Pekerja Mebel (Studi di PT Alis Jaya Ciptatama) - Triatmo, Wenang; Adi, M. Sakundarno; Hanani D., Yusniar (Jurnal Kesehatan Lingkungan Indonesia, 2006)
ABSTRACT Background : Wood dust generated from processes of sawing, planning and sanding can disperse in the workplace air and harm to the workers. Exposed to low concentration of wood dust for a long time can cause respiratory tract disorders  such as restriction, obstruction or mixed. Generally, organic dust exposure will effect on obstruction of respiratory tract which is indicated by decreasing of % FEV – 1 / FVC. Workers of wood industries have a high risk from wood dust deposition on their respiratory tract. Absorption of wood dust particles in the lung occurred by respiration mechanism. Methods : This research purpose was to analyze the exposure of wood dust and lung function disorder on furniture workers (Study  at  PT Alis Jaya Ciptatama ) in Jepara Regency. This research was an observational study with a cross Sectional approach with 55 samples. Sampling was carried out by using a Probability Systematic Sampling. Data of respirable wood dust concentration  was measured by a using Personal Dust Sampler. Whereas data of lung function was resulted from Sprirometry test  using a spirometer. Other data was collected from interview with the workers with age limitation is up to 40 years old. Data analyze by Chi Square Test was used to   identity the wood dust exposure, age, gender, time of exposure, working years, smoking habit, excercise habit, nutrient status and awareness in using of Personal Protective Equipment, in the correlation of occuring the lung function disorder.Multivariat analysis was carried out by regression test with the method of backward stepwise. Results: The result of this research was wood dust exposure significantly influence and correlate to the occuring of the lung function disorder on furniture workers ( Study at PT Alis Jaya Ciptatama ), using appliance Personal Dust Sampler, highest result wood dust exposure 1,848 mg/m³ and the low result wood dust exposure 0,833 mg/m³, with the result : for wood dust exposure  p = 0,001 and odss ratio  = 13,720 with 95% CI (3,034 – 62,040). Probability of wood dust exposure factor toward lung function disorder which was assessed by logistic regression formula resulted in, wood dust exposure over the Theshold Limit Value of 1 mg/m³ is 78,4% another 21,6% is because of other factor beyond the study of the researcher. Conclusion: The recomendation  of this research is expected to be an input for the local government and  Health Service in particular, in making guidelines of the programs related to harmful effects from the workplace to the workers health, as well as for the needs of workplace monitoring and occupational health surveillance. Therefore to make the programs succeed , it needs occupational health promotion  and application of controle measures on reducing wood dust concentration at the workplace. Keywords : Wood Dust Exposure, Lung Function Disorder, Workers, Furniture.